Design of compact microstrip patch antenna for WBAN applications at ISM 2.4 GHz - Shahid M Ali; Varun Jeoti; Tale Saeidi; Wong Peng Wen (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper introduces the design of compact microstrip patch antenna for wireless body area network (WBAN) applications at ISM 2.4 GHz. The design consists of a radiating patch on one side of the substrate and a ground plane is located on the other side of the substrate. The antenna is fed through an inset transmission line and then loaded by two triangles, and shorting pins on both sides of the radiating patch to lengthen the path for current, as result it reduced the overall size. The dimensions of radiating patch antenna are 62 mm× 43 mm × 1.67 mm. By locating the proposed antenna On and Off body communication, it can maintain compact and stable far field radiation characteristics and negligible specific absorption rate (SAR). Furthermore, high efficiencies of about 53 % and 46% are obtained during off and on body, which is higher than recent similar works in the literature. The simulated results showed a good agreement with the measured results. Owing to the acceptable results, the proposed design can be a reliable candidate for WBAN applications at ISM band.